Care of the Brain-Dead Organ Donor - Siah, Julian W. R.; Sudhan, Nazneen; Wijayatilake, Dhuleep S. (Journal of Neuroanaesthesiology and Critical Care, 2019)
There remains a worldwide shortage of organs for transplantation. If not properly cared for, the organs of patients who are brainstem dead will deteriorate, making them either unsuitable for transplantation or reducing the success rate of transplants. The Medline database was searched with no time limit in January 2019 for English publications using keywords “brainstem death physiology” and “organ donor care.” Full texts of all publications related to care of deceased donors after brainstem death (DBD) were reviewed. Those that were not relevant were excluded. An online search for publications and guidelines produced by international organizations relating to organ donation and care of the organ donor was also preformed, and the results were reviewed.Although there is a low level of evidence to support specific management strategies to optimize the care of potential DBD patients, there is reasonable consensus between different international guidelines on protocolized intensive care unit (ICU) management of potential DBD patients and donor resuscitation targets.Key management concepts include (1) early recognition of brainstem DBD and referral to organ donation services, (2) ICU-led multidisciplinary team (MDT) approach to donor management, (3) shift in ICU teams thinking from management of raised intracranial pressure (ICP) to maintaining organ perfusion and function, (4) early active donor management to normalize donor physiology, and (5) prevention, recognition, and treatment of complications of brainstem death.
Keywords: brainstem death physiology; organ donor care; organ transplant